Domestic Violence as a Phenomenon which Affects Family Safety - Zbigniew Kazimierz Mikołajczyk (The Francis de Sales Scientific Society (TNFS.PL), 2022)
Family security depends on many factors, e.g., economic, political and social. Negative social phenomena, including crime, have a significant impact on the sense of security. Crime is understood as the number of prohibited acts committed in a given area and in a given time unit. Among its various types, we distinguish crime related to the functioning of the family. This study shows the scale of domestic violence in our country in recent years. The analysis concerns numerical data on the "Blue Card" procedure collected in the police database.